Mineral Profile of Himalayan Pink and Black Salts and Their Efficacy as on in-vitro Fermentation as Compared to Conventional Salt - Singh, Jaswinder; Sharma, Amit; Arunbeer Singh; Hundal, Jaspal Singh; Chadda, Akshita (Indian Journal of Animal Nutrition, 2024)
Salt is an essential component, required for different physiological functions of the animal body. Dairy farmers in northern India are using the Himalayan rock salt since the time of yore by placing it in the manager for animal and presume that it will aid in digestions and keeping the animal healthy. Henceforth, this study was undertaken to evalaute the mineral composition of pink and black Himalayan salts and their effect on in- vitro rumen fermentation. Three concentrate mixtures viz. CSCM (Conventional salt concentrate mixture); PSCM (Pink salt concentrate mixture); BSCM (Black salt concentrate mixture) were prepared by supplementing conventional common salt, Himalayan pink and black salts at 1 % respectively. Concentrate mixture and maize silage were used in 60:40 ratio to prepare three different total mixed rations (TMR). Results revealed that sodium and chloride levels were 39.36 and 60.16; 27.8 and 42.85; 12.54 and 19.33 %, respectively in conventional, pink and black salts. Additionally, in pink and black salts, the level of iron, sulphur, magnesium and calcium were 1.10 and 5.38; 126.08 and 263.12; 66.25 and 0.88; 93.97 and 7.89 mg/100 g, respectively. Further, among heavy metal, the only Cd (0.1 ppm) was traced in the pink salt. In-vitro trials reported that there was no effect of replacing conventional salt with either pink or black on net gas production, in-vitro dry matter and organic matter digestibility, partitioning factor and microbial biomass production on substrate having either concentrate mixture or TMR. Therefore, it can be concluded that Himalayan pink and black salts could be beneficial in meeting the mineral requirement of dairy animals in economical way. However, a comprehensive in- vivo study is required to evaluate the effect of Himalayan rock salt (pink and black) on rumen fermentation and productive performance of dairy animals before drawing final recommendations.